FPR2 participates in epithelial ovarian cancer (EOC) progression through RhoA-mediated M2 macrophage polarization - Xiaohui Xie; Juan He; Qiong Wang; Yaqiong Liu; Weiwei Chen; Kun Shi (BMC, 2021)
Abstract Background In our previous study, we found that formyl peptide receptor 2 (FPR2) promoted the invasion and metastasis of epithelial ovarian cancer (EOC) and could be a prognostic marker for EOC. In this study, we aimed to study the possible mechanism of FPR2 in promoting EOC progression. Methods EOC cell lines with ectopic FPR2 expression and knockdown as well as their control cell lines were established, and the expression change of RhoA in each cell line was evaluated by real time quantitative polymerase chain reaction (RT-qPCR) and Western blot. Wound healing and Transwell assays were performed to detect the migratory ability of EOCs affected by FPR2 and RhoA. The supernatant of each EOC cell line was used to coculture with macrophages, and then we tested M1 and M2 macrophage biomarkers in the supernatants by flow cytometry. The THP-1 cell line was also induced to differentiate into M1 and M2 macrophages, and FPR2 and RhoA expression in each macrophage cell line was detected by RT-qPCR and Western blot. A tumour xenograft model was established with SKOV3 and SKOV3−shFPR2 cell lines, and tumour volumes and weights were recorded. Results RhoA expression was significantly increased in EOCs along with the overexpression of FPR2, which showed a positive correlation by Pearson correlation analysis. Ectopic FPR2 expression contributes to the migratory ability of EOCs, and a RhoA inhibitor (C3 transferase) impairs EOC migration. Furthermore, FPR2 stimulated the secretion of Th2 cytokines by EOCs, which induced macrophages to differentiate to the M2 phenotype, while a RhoA inhibitor stimulated the secretion of Th1 cytokines and induced macrophages to differentiate to the M1 phenotype. Moreover, compared with M1 macrophages and THP-1 cells, FPR2 and RhoA expression was significantly upregulated in M2 macrophages. Conclusion FPR2 stimulated M2 macrophage polarization and promoted invasion and metastasis of ovarian cancer cells through RhoA.